Inequality of opportunity, income inequality and economic mobility: Some international comparisons - Paolo Brunori; Francisco H. G. Ferreira; Vito Peragine (Institute for the Study of Labor (IZA), 2013)
Despite a recent surge in the number of studies attempting to measure inequality of opportunity in various countries, methodological differences have so far prevented meaningful international comparisons. This paper presents a comparison of ex-ante measures of inequality of economic opportunity (IEO) across 41 countries, and of the Human Opportunity Index (HOI) for 39 countries. It also examines international correlations between these indices and output per capita, income inequality, and intergenerational mobility. The analysis finds evidence of a Kuznets curve for inequality of opportunity, and finds that the IEO index is positively correlated with overall income inequality, and negatively with measures of intergenerational mobility, both in incomes and in years of schooling. The HOI is highly correlated with the Human Development Index, and its internal measure of inequality of opportunity yields very different country rankings from the IEO measure.
Keywords: D71; D91; I32; 330; equality of opportunity; income inequality; social mobility; mobility